Chicken Eggshell Powder as Antibacterial Against Staphylococcus aureus and Escherichia coli Through In Vitro Studies - Rodhiansyah Djayasinga; Rudy Tahan Mangapul Situmeang; Fuangfa Unob; Sutopo Hadi; Posman Manurung; Sumardi Sumardi (Journal of Multidisciplinary Applied Natural Science, 2024)
Identifying the most effective material with antibacterial properties against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) is a challenging task considering the rising concerns about drug resistance. Various experiments through in vitro and in vivo studies to obtain antibacterial agents using abundant and easily available raw material sources have been conducted. Therefore, this study aimed to acquire semiconducting nanoparticle material derived from purebred chicken eggshell waste that could effectively function as an antibacterial agent. The waste treatment was carried out using a top-down method applying the thermal decomposition method with calcination temperatures of 700 and 800 ºC for 30 hours. XRD analysis results showed CaO as a major phase and this was further supported by Rietveld calculation. The size of the crystalline phases obtained ranged from 10–45 nm, while FTIR analysis showed the appearance of CaO bond at a wave number of 715.65 cm-1. Furthermore, SEM analysis showed a rough folded particle surface with a pore percentage of 48.20%. Based on the UV-Vis DRS analysis results, chicken eggshell powder had band gap energy characteristics of 2.07, 2.74, 3.71, and 5.96 eV for sample B, as well as 4.60 and 5.82 eV for sample C. Activation of purebred chicken eggshell powder as antibacterial was performed both qualitatively and quantitatively using photocatalytic and non-photocatalytic methods. Qualitatively, both samples showed antibacterial activity, with a minimal inhibitory concentration (MIC) of 1,000 µg/mL.